Persepsi Iklim Keselamatan dan Kepatuhan Aspek COVID-19 Pekerja Indonesia: Studi Kasus di Perusahaan Migas - Atta Rizky Suharto (Jurnal Medika Hutama, 2021)
Safety climate is vital element put on safety in a workplace organization. Attitudes, values, opinions and actions of workers in company may contribute to the perceptions and beliefs, and it will be possibly to change in the period of time and circumstance. The pandemic of COVID-19 has disrupted many aspects of life, including work safety climate in organization. Workers should be complied with tight rules and to raise their awareness of health risk and COVID-19 protocols. The study aims to overview the relationship between safety climate and COVID-19 aspects, as evidence that new adaptive behaviors can be implemented in the workplace. The study included 30 participants of oil and gas workers through online survey to assess demographic characteristics, health risks, outdoor activities, COVID-19 protocols and safety climate dimensions. Data set was performed with SPSS 24.0 to analyze safety climate items based on health risks, the possibility of outdoor exposures and the compliance of COVID-19 health protocols through independent-samples T test. The research study resulted those personal priorities and need for safety (p= 0.005) has different means among worker group with high and low health risk. Meanwhile communication perceived (p= 0.007) towards COVID-19 health protocols compliance has significant mean gap. In conclusion, the study will be utilized as pioneered evidence to make a further research about safety climate and COVID-19 aspects, which will be impactful to identify the perception in safety of organization.